The impact of habitual exercise on glycaemic control - Teo, Zachary Ian Shern (2017)
Introduction: To complement current evidence on the beneficial effects of exercise intervention on cardiometabolic risk factors, a study was conducted to investigate the effects of habitual exercise on glucose regulation. It was hypothesised that habitual exercise would have an effect on improving glucose regulation by lowering fasting, peak and postprandial glucose levels as well as a quicker return to baseline. Methods: Sixteen healthy active or sedentary participants were recruited for an oral glucose tolerance test. Participants underwent baseline plasma glucose measurements followed by ingestion of a 75 mg dextrose drink and plasma glucose concentrations were measured at half hour intervals up till the 2 h mark. Participants underwent a full medical clearance and gave informed consent prior to all trials. All trials were conducted in accordance with NTU Institutional Review Board (IRB) approved protocols. Results: A two factor analysis of variance (ANOVA) was conducted to investigate the contribution of activity and time to sample variance. The variance attributed to activity (6.93, 4.86% of total, p=0.0164) and time (60.42, 42.33% of total, p=0.613x10-7), contributed significantly to the variance of the sample data. To investigate the interaction between the two factors, Sidak’s multiple comparisons test was also performed. Only the sedentary group had a significant increase in glucose concentrations (2.013, p=0.0032) from 0.0 h to 1.0 h. Conversely, only the active group (-1.852, p=0.0007) had a significant decrease in glucose concentrations from 0.5 h to 1.5 h. Discussion: The results suggest that active participants may have had better time-specific glucose regulation, and that self-reported activity levels may be explored as a surrogate predictor of diabetes risk in otherwise healthy individuals. Habitual exercise was also shown to have significant impact on glucose levels, suggesting potential for therapeutic use in diabetic patients.